2016
DOI: 10.5021/ad.2016.28.6.684
|View full text |Cite
|
Sign up to set email alerts
|

Four Years Prospective Study of Natural History of Atopic Dermatitis Aged 7~8 Years at an Individual Level: A Community-Based Survey by Dermatologists' Skin Examination in Childhood

Abstract: BackgroundThe age-dependent change in atopic dermatitis (AD) at an individual level has mostly performed in a hospital-setting.ObjectiveWe evaluated the age-dependent change of AD symptoms at an individual level in a community-setting.MethodsFor the diagnostic accuracy, all participants of schoolchildren were received skin examination by dermatologists (twice a year for the same group), instead of questionnaire-based surveys. For this study, sequential check-ups of 273 elementary school children, aged 7~8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Most AD patients are diagnosed with mild disease during childhood ( 2 ). In a 4-year prospective study, Kim et al ( 20 ) found mild severity in 70% of the children with AD.…”
Section: Discussionmentioning
confidence: 98%
“…Most AD patients are diagnosed with mild disease during childhood ( 2 ). In a 4-year prospective study, Kim et al ( 20 ) found mild severity in 70% of the children with AD.…”
Section: Discussionmentioning
confidence: 98%